Conductive core-sheath type polyester composite fiber
Patent Information
- Application Number
- JP2025058782
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本発明の導電性芯鞘型ポリエステル複合繊維は芯部にポリブチレンテレフタレート(PBT)中に特定量の導電性成分を含む樹脂組成物を使用し、鞘部に特定の組成からなるポリエステル樹脂を使用し、さらに芯部と鞘部の質量比を特定範囲とすることで、高い電気抵抗値を示す繊維とすることができる。また、紡糸操業性や耐久性にも優れるものであり、こうした本発明の導電性芯鞘型ポリエステル複合繊維を用いて作製したブラシは、例えば、バイアスクリーニングブラシ等に使用した際には微細な粉塵又は汚れを高効率に吸着でき、電子写真記録方式の乾式複写機、ファクシミリ、又はプリンター等の精密機器製品、又はそれらの製造工程で用いられる帯電ブラシやクリーナーブラシに特に好適に用いられる。
Smart Images

Figure 2026166061000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a conductive core-sheath type polyester composite fiber. [Background technology]
[0002] Charging brushes, static elimination brushes, cleaning brushes, etc., are used in precision equipment such as electrophotographic dry-type copiers, facsimile machines, and printers. Cleaning with a cleaning brush is performed using a method called bias cleaning. In this method, a voltage with the opposite polarity to the charge of the charged toner is applied to the cleaning brush, causing the toner to be electrostatically attracted to the brush and removed. Therefore, from the viewpoint of improving the toner removal rate, it is preferable to have a brush that can attract more toner, and for this reason, it is desirable for the fibers used in bias cleaning to generate a strong electric field when a voltage is applied and to have a large capacitance.
[0003] Conductive fibers are used in the various brushes mentioned above. Examples of conductive fibers include those made from conductive resins containing carbon black as a conductive component within resins such as polyester resin or polyamide resin. Among these, various core-sheath composite fibers have been proposed, in which a conductive resin is placed in the core and a non-conductive resin in the sheath, in order to achieve electrical resistance values and strength suitable for various brush applications, and to produce fibers with minimal variation in electrical resistance.
[0004] For example, Patent Document 1 specifically describes a core-sheath composite fiber that can suppress variations in electrical resistance even in the high-resistance range. This fiber has a conductive resin made of polyethylene terephthalate resin (PET) and carbon black in the core, homo-PET in the sheath, and a specific range for the thickness of the sheath. Patent Document 2 also proposes a core-sheath composite fiber in which the core is a conductive layer and the sheath is an insulating layer. By setting the thickness of the sheath to a specific range, it is possible to suppress charge injection from the conductive part to attached materials when a voltage is applied to the fiber. Specifically, this core-sheath composite fiber has a conductive resin mainly composed of polyamide resin in the core and polyamide resin in the sheath.
[0005] However, the core-sheath type composite fibers described in Patent Documents 1 and 2 had insufficient performance in removing toner and other substances. Furthermore, there was room for improvement in terms of operability and durability, such as the yarn bending that occurred during spinning and the tendency for the core and sheath to separate after repeated use. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2016-69786 [Patent Document 1] Japanese Patent Publication No. 2014-102454 [Overview of the project] [Problems that the invention aims to solve]
[0007] The present invention aims to solve the above-mentioned problems and provides a conductive core-sheath type polyester composite fiber in which the core is composed of a conductive component and the sheath is composed of a non-conductive component, which is particularly suitable for use as a cleaning brush for bias cleaning due to its excellent toner removal performance. [Means for solving the problem]
[0008] The present inventors have discovered that the above problems can be solved by using specific resins for the core and sheath portions, and by creating a conductive core-sheath type polyester composite fiber in which the mass ratio of the core to the sheath portion is within a specific range, thereby setting the cross-sectional resistance value within a specific range, and have arrived at the present invention.
[0009] In other words, the present invention is summarized in the following (1) to (3). (1) A core-sheath type polyester composite fiber comprising a core portion and a sheath portion, wherein the core portion is composed of a core-forming composition mainly containing polybutylene terephthalate and containing 20 to 35% by mass of a conductive component, and the sheath portion is composed of a core-forming composition made of a polyester resin mainly consisting of ethylene terephthalate as repeating units and containing 1 to 15 mol% of isophthalic acid per 100 mol% of acid component, the total fineness is 90 to 400 dtex, the mass ratio of the core portion to the sheath portion (core portion / sheath portion) in a cross section perpendicular to the longitudinal direction of the yarn is 35 / 65 to 65 / 35, and the cross-sectional resistance is 5.0 × 10 3 ~1 × 10 6 A conductive core-sheath type polyester composite fiber with a density of Ω / cm. (2) A conductive core-sheath type polyester composite fiber as described in (1), wherein the boiling water shrinkage rate is 7% or less. (3) A brush containing conductive core-sheath type polyester composite fibers as described in (1) or (2). [Effects of the Invention]
[0010] The conductive core-sheath type polyester composite fiber of the present invention uses a resin composition containing a specific amount of conductive component in polybutylene terephthalate (PBT) for the core part, a polyester resin having a specific composition for the sheath part, and further sets the mass ratio of the core part to the sheath part within a specific range, whereby the fiber can be made to exhibit a high electrical resistance value. It also has excellent spinning operability and durability, and brushes produced using such a conductive core-sheath type polyester composite fiber of the present invention can, for example, when used as a bias cleaning brush or the like, adsorb fine dust or dirt with high efficiency, and are particularly suitably used for charging brushes and cleaner brushes used in precision equipment products such as electrophotographic recording system dry-type copying machines, facsimiles, or printers, or in their manufacturing processes. Brief Description of the Drawings
[0011] [Figure 1] This is an example of a cross-sectional view in the direction perpendicular to the longitudinal direction of the yarn of the conductive core-sheath type polyester composite fiber of the present invention. Modes for Carrying Out the Invention
[0012] Hereinafter, the present invention will be described in detail.
[0013] 1. Conductive core-sheath type polyester composite fiber The conductive core-sheath type polyester composite fiber of the present invention (hereinafter sometimes referred to as "core-sheath composite fiber") is a composite fiber composed of a core part and a sheath part. The core part of the core-sheath composite fiber contains polybutylene terephthalate (PBT) and a conductive component, and has conductivity. On the other hand, the sheath part is composed of a polyester resin containing a specific amount of isophthalic acid, and is non-conductive.
[0014] The core part is composed of a core part-forming composition that mainly contains polybutylene terephthalate and contains a conductive component, with the content ratio of the conductive component being 20 to 35 mass% relative to the total amount of the core part. Here, "mainly containing polybutylene terephthalate" means that the core part-forming composition contains 50 mass% or more of polybutylene terephthalate.
[0015] The content of the conductive component in the core-forming composition is preferably in the range of 22 to 30% by mass, and more preferably in the range of 22 to 27% by mass. By adjusting the content of the conductive component within the above range, the electrical resistance value (surface resistance value and cross-sectional resistance value) of the core-sheath composite fiber described later can be made to have a desired value.
[0016] In other words, if the content of conductive components in the core is less than 20% by mass, the electrical resistance of the core becomes too high, and the electrical resistance of the core-sheath composite fiber may not satisfy the specific range described later, resulting in poor dirt removal performance when used in bias cleaning brushes, etc. On the other hand, if the content of conductive components in the core exceeds 35% by mass, the electrical resistance of the core-sheath composite fiber may not satisfy the specific range described later, and the high concentration of conductive components makes it difficult to uniformly disperse them in the core-forming composition, leading to peeling between the core and sheath and yarn breakage during the spinning and drawing process, resulting in core-sheath composite fibers that are inferior in strength and durability of conductive performance.
[0017] Examples of conductive components used in the present invention include conductive carbon black, metal powders (silver, nickel, copper, iron, tin, or alloys thereof), and metal compounds such as copper sulfide, copper iodide, zinc sulfide, and cadmium sulfide. Conductive particles can also be obtained by adding a small amount of antimony oxide to tin oxide or a small amount of aluminum oxide to zinc oxide. Furthermore, conductive particles can be obtained by coating the surface of titanium oxide with tin oxide and mixing and firing it with antimony oxide. Among these, conductive carbon black (e.g., furnace black, acetylene black, Ketjen black, etc.) is preferred because it is commonly used to improve the performance of conductive fibers and does not hinder the fluidity of polymers as much as metal particles.
[0018] The average particle size of conductive carbon black is preferably 0.015 μm or more and 1 μm or less, and more preferably 0.020 μm or more and 0.5 μm or less. Using conductive carbon black with an average particle size of 1 μm or less makes it easier to obtain a stable electrical resistance value. This is because the smaller the average particle diameter of the carbon black, the larger the surface area, making it easier to stabilize conductivity and thus suppressing variations in electrical resistance. In addition, carbon black with an average particle size of 1 μm or less has good dispersibility, resulting in better operability. On the other hand, if the average particle size of the carbon black is less than 0.015 μm, aggregation is likely to occur, which can reduce operability, and the connections (structure) between carbon black particles may not be well formed, which can lead to variations in electrical resistance in the longitudinal direction of the yarn.
[0019] The resistivity of the conductive component is 1 × 10⁻⁶ 4 Preferably, the size is Ω·cm or less, and 1 × 10 2 Resistivity values of Ω·cm or less are more preferable. 4 Using conductive particles exceeding Ω·cm may necessitate dispersing a large amount of conductive particles within the polymer to achieve the desired conductivity. This not only adversely affects the physical properties of the core-sheath composite fiber but can also cause yarn breakage during spinning and drawing, potentially leading to operational problems.
[0020] In this invention, PBT is primarily used as the resin constituting the core. Because PBT is a highly crystalline resin, the conductive components it contains are easily arranged uniformly within the PBT, resulting in less variation in the electrical resistance value along the longitudinal direction of the yarn. Furthermore, PBT is considered to have higher insulating properties than polyethylene terephthalate (PET), which allows for a higher electrical resistance value in the core. In this invention, by using PBT as the resin constituting the core and further setting the mass ratio of the core to the sheath to a specific range, it is possible to obtain a core-sheath composite fiber with the electrical resistance value described later, thereby obtaining a fiber suitable for bias cleaning brush applications.
[0021] PBT may contain copolymer components as long as they do not impair the effects of the present invention, but it is preferable that it does not contain copolymer components. Examples of copolymer components include ethylene glycol (EG), cyclohexanedimethanol (CHDM), cyclohexanedicarboxylic acid (CHDA), isophthalic acid (IPA), 1,3-propanediol, sebacic acid, dimer acid, dodecanedioic acid, xylylene glycol, polytetramethylene glycol, polyethylene glycol, epsilon caprolactam, and the like.
[0022] The PBT content in the core-forming composition is 50% by mass or more, preferably 55% by mass or more, more preferably 60% by mass or more, even more preferably 65% by mass or more, even more preferably 70% by mass or more, and particularly preferably 75% by mass or more. The resin constituting the core may also contain polyester resins other than PBT, such as polyethylene terephthalate or copolymerized polyester resins, as long as the effects of the present invention are not impaired. However, in the present invention, it is preferable to use only PBT as the resin constituting the core.
[0023] Next, the sheath will be described. The sheath is composed of a sheath-forming composition mainly consisting of a polyester resin, in which ethylene terephthalate is the main repeating unit and isophthalic acid is present in an amount of 1 to 15 mol% per 100 mol% of the acid component. Here, "mainly consisting of ethylene terephthalate as the main repeating unit" means that the repeating units of ethylene terephthalate account for 50 mol% or more of the total repeating units constituting the polyester resin. Also, "mainly containing polyester resin" means that the sheath-forming composition contains 50% by mass or more of polyester resin.
[0024] The polyester resin has ethylene terephthalate as the main repeating unit and contains 1 to 15 mol% of isophthalic acid per 100 mol% of the acid component. The content of the ethylene terephthalate repeating unit is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 85 mol% or more, and even more preferably 90 mol% or more. Isophthalic acid is included as a copolymer component, and the content of isophthalic acid is preferably 2 to 12 mol%, more preferably 4 to 12 mol%, and even more preferably 6 to 10 mol% per 100 mol% of the acid component. By copolymerizing the polyester resin with isophthalic acid in the above content, the reaction temperature during the polycondensation reaction and the spinning temperature can be lowered. That is, the difference in melt viscosity with the core-forming composition constituting the core is reduced, and the composite spinning process can be carried out smoothly.
[0025] If the isophthalic acid content in the polyester resin is less than 1 mol% per 100 mol% of the acid component, the melting point cannot be lowered compared to the PBT contained in the core-forming composition, and the polycondensation reaction temperature and spinning temperature cannot be reduced, making it difficult to carry out the composite spinning process smoothly. On the other hand, if the isophthalic acid content exceeds 15 mol%, the amorphous region in the fiber increases, which tends to worsen operability during spinning, and even if a core-sheath composite fiber can be obtained, the strength and conductivity of the obtained core-sheath composite fiber will decrease. In addition, it becomes difficult to control the boiling water shrinkage rate, and the boiling water shrinkage rate tends to be high.
[0026] The polyester resin may contain other copolymerization components, as long as they do not impair the effects of the present invention. Examples of other copolymerization components include cyclohexanedimethanol (CHDM) and cyclohexanedicarboxylic acid (CHDA).
[0027] The sheath-forming composition contains 1 to 15 mol% of isophthalic acid in a polyester resin, which is 50% by mass or more, preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 85% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably 100% by mass.
[0028] The total fineness of the core-sheath composite fiber of the present invention is 90 to 400 dtex, preferably 100 to 300 dtex, and more preferably 110 to 250 dtex. Furthermore, the core-sheath composite fiber of the present invention is preferably a multifilament formed by twisting together multiple single filaments, and the number of single filaments constituting the multifilament is preferably 20 to 60. The single filament fineness of the core-sheath composite fiber can be appropriately adjusted depending on the application, for example, preferably 2.0 to 20.0 dtex, more preferably 2.0 to 10.0 dtex, and even more preferably 3.0 to 8.0 dtex. If the single filament fineness satisfies the above range and is thin, the surface area of the core-sheath composite fiber will increase, and the dust removal performance when used in bias cleaning brushes and the like can be greatly improved. The single filament fineness and total fineness of the core-sheath composite fiber in this invention are values measured based on "Method A" of "8.3.1 Correct Fineness" in JIS L1013:2010 Chemical Fiber Filament Yarn Testing Method.
[0029] Next, a cross-section perpendicular to the longitudinal direction of the core-sheath composite fiber of the present invention will be described. Figure 1 is an example of a cross-sectional view perpendicular to the longitudinal direction of the core-sheath composite fiber. As shown in Figure 1, in the core-sheath composite fiber 1 of the present invention, the sheath portion 2 covers the surface of the core portion 3.
[0030] In the cross-section of a core-sheath composite fiber, it is preferable that the shape of the core and the shape of the sheath are substantially identical and substantially concentric. If the shapes of the core and the sheath are different, or if their shapes are the same but their centers are different, the thickness of the sheath on the fiber surface will not be uniform, which may lead to a large variation in electrical resistance.
[0031] In core-sheath composite fibers, the mass ratio of the core portion to the sheath portion (core portion / sheath portion) in a cross-section perpendicular to the longitudinal direction of the yarn is in the range of 35 / 65 to 65 / 35, preferably in the range of 35 / 65 to 60 / 40, and more preferably in the range of 40 / 60 to 60 / 40.
[0032] In this invention, by setting the mass ratio of the core to the sheath within the above range, the core-sheath composite fiber will have the electrical resistance value described later, making it a fiber suitable for bias cleaning applications. That is, if the ratio of the sheath to the core is too large, the thickness of the sheath becomes too large, reducing the capacitance, and the charge retention performance in the sheath when a voltage is applied to the fiber will be poor. Therefore, when a voltage is applied to the brush as a bias cleaning brush, there is a risk that a sufficient electric field for electrostatic attraction cannot be applied to the tip of the brush fiber.
[0033] On the other hand, if the ratio of the sheath to the core is too small, the capacitance increases due to the reduced thickness of the sheath, but the overall electrical resistance of the yarn decreases due to the increased proportion of the core, and there is a risk of dielectric breakdown in the sheath when voltage is applied to the fiber. Dielectric breakdown means that the insulating performance of the sheath is destroyed as a result of applying a voltage higher than the withstand voltage of the insulating layer of the sheath, making it impossible to retain charge and causing excessive current to flow out. Therefore, when voltage is applied to the brush as a bias cleaning brush, dielectric breakdown in the sheath may occur, causing excessive charge to flow into the material being cleaned, which may reduce the cleaning performance.
[0034] In this invention, by setting the mass ratio of the core to the sheath within a specific range and using PBT as the resin constituting the core, it is possible to make the core-sheath composite fiber have both high electrical resistance and high capacitance.
[0035] For the single filament constituting the core-sheath composite fiber, the thickness of the sheath portion in the cross section perpendicular to the longitudinal direction of the yarn is preferably 1.5 to 4.5 μm, more preferably 1.6 to 4.2 μm, and even more preferably 1.8 to 4.0 μm. When the thickness of the sheath portion is within the above range, the sheath portion has a certain thickness, which can suppress excessive outflow of electric charge to the outside caused by dielectric breakdown occurring in the sheath portion when a voltage is applied to the fiber.
[0036] 2. Physical properties of conductive core-sheath type polyester composite fiber Next, regarding the electrical resistance values of the core-sheath composite fiber, two types of characteristic values are described below.
[0037] The first characteristic value, which is the electrical resistance value in the cross section in the longitudinal direction of the yarn of the core-sheath composite fiber (hereinafter sometimes referred to as "cross-sectional resistance value"), is 5.0×10 3 ~1×10 6 Ω / cm, and is preferably in the range of 1×10 4 ~1×10 6 Ω / cm. When the cross-sectional resistance value is 5.0×10 3 Ω / cm or more, it is possible to suppress excessive movement of electric charge from the core portion when a potential is applied to the fiber, and prevent the occurrence of dielectric breakdown in the sheath portion. On the other hand, when the cross-sectional resistance value is 1×10 6 Ω / cm or less, when a voltage is applied to the fiber as a bias cleaning brush, an electric field sufficient for electrostatic adsorption can be applied to the tip of the brush fiber, and a sufficient electrostatic capacity can be imparted to the core-sheath composite fiber. The cross-sectional resistance value can be adjusted by appropriately changing the content (concentration) of the conductive component in the core portion, the mass ratio of the core portion to the sheath portion, and the like.
[0038] The second characteristic value, which is the electrical resistance value on the surface in the longitudinal direction of the yarn of the core-sheath composite fiber (hereinafter sometimes referred to as "surface resistance value"), is preferably 1×10 8 ~1×10 13 Ω / cm, more preferably 1×10 9 ~1×10 11 Ω / cm, even more preferably 4×10 9 ~1×1010 It is even more preferable that the surface resistance is Ω / cm. In this invention, by setting the mass ratio of the core to the sheath, the thickness of the sheath, or the content of conductive components in the core to a specific range, the surface resistance can be increased to 1 × 10⁻⁶. 8 ~1 × 10 13 This allows the resistance to be expressed as Ω / cm, and also makes it possible to suppress variations in surface resistance.
[0039] In this invention, the two types of electrical resistance values mentioned above are measured by the following method. First, 20 test pieces, each 10 cm long, are taken every 100 m along the longitudinal direction of the core-sheath composite fiber (multifilament). Next, a voltage of 50 V is applied to both ends of each test piece, and the electrical resistance is measured using a resistance meter (SM-10E, manufactured by Toa Denpa Kogyo Co., Ltd.) in an environment of 20°C and 20% RH relative humidity. The average value of the measurement results for the 20 test pieces is then calculated. When measuring the cross-sectional resistance, a conductive paste (Fukuda Denshi Co., Ltd., product name "Keratin Cream", model "OJE-01D") is applied to the cross-section along the longitudinal direction of the core-sheath composite fiber (multifilament), and the voltage is applied only to the cross-section. To measure the surface resistance, the voltage is applied only to the surface along the longitudinal direction of the core-sheath composite fiber (multifilament).
[0040] The CV value (unit: %) is an index that indicates the variation in the surface resistance of core-sheath composite fibers. The CV value is measured by the following method: Twenty 10cm long test pieces are taken every 100m along the longitudinal direction of the core-sheath composite fiber (multifilament), the surface resistance of each test piece is measured, and the average value is calculated. Then, the CV value is calculated according to the following formula (1). Surface resistance CV value (%) = (V / X) × 100 (1)
[0041] In equation (1) above, V represents the square root of the unbiased variance of the surface resistance value, and X represents the surface resistance value (average value of 100 test specimens). The unbiased variance is calculated by determining the difference between the measured surface resistance value of each of the 100 test specimens and the average surface resistance value of each specimen, squaring these differences, and then dividing the sum of the squared values by (number of test specimens - 1).
[0042] The CV value is preferably 20% or less, more preferably 10% or less, and even more preferably 6% or less. If the CV value exceeds 20%, variations in surface resistance occur, making it difficult to achieve uniform charging, static discharge, or cleaning when used in components for devices such as electrophotographic dry-type copiers, facsimile machines, or printers (e.g., charging brushes, static discharge brushes, or cleaning brushes). In this invention, the CV value can be kept within the above range by using PBT as the resin constituting the core, making the shape of the core and the shape of the sheath substantially the same and concentric with each other, or by spinning the yarn so that the thickness of the sheath is uniform.
[0043] The core-sheath composite fiber of the present invention preferably has a shrinkage rate of 7% or less, and more preferably 5% or less, after boiling water treatment for 30 minutes. If the boiling water shrinkage rate exceeds 7%, the fiber becomes more prone to deformation when heat treatment is applied in subsequent processes (e.g., dyeing processes), which changes the dispersion state of the conductive components contained in the core. As a result, the cross-sectional resistance value changes significantly before and after heat treatment, making it difficult to obtain a stable electrical resistance value. To achieve a boiling water shrinkage rate of 7% or less, for example, the content of IPA in the resin constituting the sheath can be adjusted, or the heat treatment temperature during stretching can be appropriately adjusted.
[0044] The core-sheath composite fiber of the present invention preferably has a breaking strength of 1.6 cN / dtex or higher, more preferably 1.8 cN / dtex or higher, and even more preferably 1.9 cN / dtex or higher. In the present invention, there is no particular upper limit to the breaking strength of the core-sheath composite fiber, but it is preferably around 6.5 cN / dtex. Furthermore, the elongation at break is preferably 40 to 70%, more preferably 45 to 66%, and even more preferably 45 to 58%. In the present invention, by setting the breaking strength within the above range, the core-sheath composite fiber has appropriate strength and durability, and has rigidity when used as a brush, for example, so that bristles do not easily collapse. Furthermore, by setting the elongation at break within the above range, it is possible to make it strong against friction between fibers when used as a brush, for example, and to make it possible to have excellent durability in dust removal performance. Furthermore, in this invention, by constructing the core and sheath portions from the above-mentioned specific resin composition, or by adjusting the mass ratio of the core and sheath portions to the above-mentioned specific range, the fibers can be manufactured with good operability, and as a result, the breaking strength and breaking elongation can be adjusted to the above-mentioned range.
[0045] The tensile strength of the core-sheath composite fiber in this invention is a value measured according to JIS-L-1013:2010 Chemical Fiber Filament Yarn Testing Method 8.5 "Tensile Strength and Elongation" 8.5.1 "Standard Time Test". Specifically, a conductive composite fiber is used as the sample, and the strength is measured when the sample breaks under elongation conditions of a sample yarn length of 10 cm and a tensile speed of 10 cm / min using a tensile testing machine.
[0046] Furthermore, the elongation at break is a value measured according to JIS-L-1013:2010 Chemical Fiber Filament Yarn Testing Method 8.5 "Tensile Strength and Elongation" 8.5.1 "Standard Time Test". Specifically, the obtained conductive composite fiber is used as a sample, and the elongation is measured when the sample breaks under conditions of a sample yarn length of 10 cm and a tensile speed of 10 cm / min using a tensile testing machine.
[0047] The core-sheath composite fiber of the present invention may be subjected to known processes such as false twisting. Alternatively, it may be used in combination with other fibers by interlacing, taslan processing, etc.
[0048] 3. Brush The core-sheath composite fiber of the present invention is suitably used not only in clothing applications (e.g., antistatic work clothes or uniforms), interior applications (e.g., curtains), or industrial materials applications, but also in components used in devices such as electrophotographic dry-type copiers, facsimile machines, or printers (e.g., electrostatic brushes, antistatic brushes, or cleaning brushes). In particular, it is suitably used in precision equipment products such as electrophotographic dry-type copiers, facsimile machines, or printers, or in electrostatic brushes or cleaning brushes used in their manufacturing processes.
[0049] Next, a brush using the core-sheath composite fiber of the present invention will be described. The brush of the present invention uses at least a portion of the core-sheath composite fiber of the present invention, preferably with a proportion of 50% by mass or more of the core-sheath composite fiber of the present invention in the brush, and more preferably consisting solely of the core-sheath composite fiber of the present invention. The form of the brush is not particularly limited, but one example is a brush made by weaving the core-sheath composite fiber of the present invention into a pile fabric, cutting this pile fabric into a tape shape, and spirally winding it around the surface of a cylindrical shaft. Another example is a brush made by cutting the core-sheath composite fiber of the present invention into short fibers, adhering them to a fabric surface by flocking, similarly forming this fabric into a tape shape, and spirally winding it around the surface of a shaft. Furthermore, in the brush of the present invention, after spirally winding the pile fabric or the like around the surface of the shaft as described above, it is preferable to perform heat setting by hot water treatment to open the fibers on the surface of the brush and smooth the surface of the brush.
[0050] 4. Method for manufacturing conductive core-sheath type polyester composite fibers The following describes an example of a method for producing the core-sheath composite fiber of the present invention.
[0051] First, as a method for obtaining the core-forming composition that forms the core, a known PBT resin (polybutylene terephthalate) and a conductive component are kneaded together. Examples of kneading methods include mixing the conductive component with PBT resin pellets (resin pellets) and melt-kneading the two together; preparing PBT resin pellets and master pellets containing the conductive component in advance, mixing the two together, and melt-kneading them together; and adding the conductive component to molten PBT resin and kneading it together. In particular, in order to uniformly disperse the conductive component in the PBT resin, it is preferable to obtain the composition by mixing carbon black with PBT resin pellets and melt-kneading them together.
[0052] Next, as a method for obtaining the sheath-forming composition that constitutes the sheath, one can obtain it by melting a polyester resin that mainly uses ethylene terephthalate as the repeating unit and contains 1 to 15 mol% isophthalic acid per 100 mol% of the acid component using a known method for producing copolymer polyester, or by purchasing a commercially available polyester resin.
[0053] Next, the obtained core-forming composition and sheath-forming composition are used to form chips by drying or other treatments as necessary, and then kneaded and melted using a conventional composite spinning apparatus, for example, in an extruder. After that, melt spinning is performed by extruding the material through a core-sheath type spinneret using a composite melt spinning apparatus having multiple spinning holes.
[0054] In composite melt spinning, the shear rate at the spinning temperature is 1000 s. -1 The difference in melt viscosity between the core-forming composition and the sheath-forming composition (melt viscosity of the sheath-forming composition - melt viscosity of the core-forming composition) is 300 dPa·s. -1 It is preferable to adjust the following (absolute value): The difference in melt viscosity between the core-forming composition and the sheath-forming composition should be reduced to (300 dPa·s). -1By performing composite spinning using the following (absolute values) method, the adhesion between the resins of the core and sheath during spinning is improved, resulting in smoother extrusion from the tip nozzle. Furthermore, the resulting undrawn yarn (core-sheath composite fiber) is less prone to separation between the core and sheath. Therefore, the resulting core-sheath composite fiber has excellent strength and durability.
[0055] The spinning temperature is preferably 250-310°C, more preferably 260-290°C, and even more preferably 260-280°C. If the spinning temperature is too high, the resin in the core and sheath will undergo thermal decomposition, making smooth spinning difficult and potentially degrading the physical properties such as strength and elongation, as well as the conductivity of the resulting core-sheath composite fiber. On the other hand, if the spinning temperature is too low, undissolved material is likely to remain, which can easily cause the yarn to break during spinning.
[0056] Next, the obtained undrawn yarn is cooled by an airflow, an oil agent is applied to the surface, and then it is wound up at a speed of 2000 to 3000 m / min. The winding speed is preferably 2400 to 2900 m / min, and more preferably 2600 to 2800 m / min.
[0057] The undrawn yarn is heated at 50-100°C and drawn to a length of 1.2-2.0 times. Preferably, it is drawn to a length of 1.4-1.8 times while heated at 70-100°C, and most preferably at 85-98°C. Drawing at the above temperatures and ratios results in a uniform distribution of conductive components along the length of the fiber, yielding a core-sheath composite fiber with superior conductivity and strength.
[0058] Next, the stretched yarn is heat-treated at 130-160°C and then wound up. The heat treatment is preferably performed at 135-155°C. By performing the heat treatment at temperatures within the above range, the boiling water shrinkage rate of the core-sheath composite fiber can be reduced, resulting in a stable electrical resistance value.
[0059] In the manufacturing method of the present invention, a method of stretching can be employed in which the rotational speed is changed between the first roller and the second roller, and it is preferable to provide a heat plate between the first roller and the second roller and perform heat treatment at 130 to 160°C. [Examples]
[0060] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. The measurement or evaluation method for the conductive core-sheath type polyester composite fiber obtained in the examples is as follows.
[0061] 1. Cross-sectional electrical resistance value The obtained conductive core-sheath type polyester composite fiber was used for measurement by the method described above.
[0062] 2. Surface resistance value and CV value The surface resistance of the obtained conductive core-sheath type polyester composite fiber was measured using the method described above. Then, the unbiased variance was determined using the obtained surface resistance value and the method described above.
[0063] 3. Boiling water shrinkage rate The obtained conductive core-sheath type polyester composite fibers were treated with boiling water for 30 minutes according to the JIS L-1013-7.15B method, and the yarn length (L') after air drying and the yarn length (L) before treatment were measured and calculated using the following formula. Boiling water shrinkage rate (%) = [(LL′) / L] × 100
[0064] 4. Thickness of the sheath Five single filaments were taken from the obtained conductive core-sheath composite multifilament fibers. Cross-sections perpendicular to the longitudinal direction of the fibers were photographed using an electron microscope (KEYENCE VHX-600 microscope) (magnification: 1000x), and the thickness of the sheath portion of each filament was determined. The average value of these measurements was taken as the thickness of the sheath portion.
[0065] 5. Breaking strength and elongation at break The obtained conductive core-sheath type polyester composite fibers were measured according to JIS-L-1013:2010 Chemical Fiber Filament Yarn Testing Method 8.5 "Tensile Strength and Elongation" 8.5.1 "Standard Time Test". Specifically, the obtained conductive core-sheath type polyester composite fibers were used as samples, and the strength and elongation were measured at the point of stretching and breaking of the sample using a Tensilon RTC-1210 (manufactured by Orientec Co., Ltd.) under conditions of a sample yarn length of 10 cm and a tensile speed of 10 cm / min.
[0066] 6. Operability In manufacturing conductive core-sheath type polyester composite fibers, melt spinning was performed continuously for 24 hours. The number of yarn breaks per spindle during spinning was evaluated in three stages as follows. ○...The number of times the thread broke was 10 or less. △··The number of times the thread broke was between 11 and 19. ×...The thread broke more than 20 times.
[0067] <Example 1> (1) Manufacturing of the core-forming composition A slurry of terephthalic acid (TPA) and ethylene glycol (EG) was supplied to an esterification reactor and reacted under conditions of 250°C and 50 hPa, yielding a reaction product with an esterification reaction rate of 95%. A slurry consisting of isophthalic acid (IPA) and ethylene glycol was placed in another esterification reaction vessel, and the esterification reaction was carried out at a temperature of 200°C for 3 hours to obtain a reaction solution of isophthalic acid and ethylene glycol. The reaction product of TPA and EG, a reaction solution of isophthalic acid and ethylene glycol, and a polymerization catalyst are added, and the reactor is subjected to a reduced pressure to carry out a melt polymerization reaction, resulting in a copolymerized polyester resin (8 mol% IPA copolymerized as the acid component, with a melting point of 234°C and a melt viscosity of 1340 dPa·s). -1 A core-forming composition containing only the copolymerized polyester resin was obtained.
[0068] (2) Manufacturing of the sheath-forming composition PBT is mixed with conductive carbon black to a content of 25% by mass, resulting in a melting point of 223°C and a melt viscosity of 1450 dPa·s. -1 A sheath-forming composition was obtained.
[0069] (3) Manufacturing of core-sheath type composite fibers The core-forming composition and sheath-forming composition described above were prepared and supplied to a composite spinning apparatus. Melt spinning was performed using a spinneret designed so that the fiber cross-sectional shape would be as shown in Figure 1. At this time, the mass ratio of the core to the sheath (core / sheath) was 40 / 60, and the sheath was arranged to cover the entire surface of the core. The spinning temperature was 270°C and the shear rate was 1000 s. -1 The difference in melt viscosity between the core-forming composition and the sheath-forming composition (melt viscosity of the sheath-forming composition - melt viscosity of the core-forming composition) is 110 dPa·s. -1 The process involved melt-spun yarn from a die nozzle, then cooling it by blowing cooling air (28°C, wind speed 0.4 m / s) from a position 120 mm downwards from the bottom surface of the die nozzle. After bundling and oiling, the yarn was wound up at a speed of 2700 m / min on a take-up roller to obtain a partially undrawn yarn. The obtained partially undrawn yarn was then heat-treated between a first roller (temperature 90°C) and a second roller (room temperature) using a 150°C heater plate, and stretched to a stretch ratio of 1.7 times, thereby winding up a conductive core-sheath type polyester composite fiber (130 dtex / 24 f).
[0070] <Example 2, Comparative Example 1> Except for changing the mass ratio of the core-forming composition and the sheath-forming composition to those shown in Table 1, melt spinning, drawing, and winding were performed in the same manner as in Example 1 to obtain a conductive core-sheath type polyester composite fiber with a density of 130 dtex / 24f.
[0071] Table 1 shows the characteristic values and evaluation results of the conductive core-sheath type polyester composite fibers obtained in Examples 1 and 2 and Comparative Example 1.
[0072] [Table 1]
[0073] The conductive core-sheath type polyester composite fibers obtained in Examples 1 and 2 used specific resins for the core and sheath portions, respectively, and the mass ratio of the core to the sheath portion satisfied a specific range. As a result, both the cross-sectional resistance and surface resistance were high, making them suitable as cleaning brushes for bias cleaning brushes.
[0074] On the other hand, the conductive core-sheath type polyester composite fiber obtained in Comparative Example 1 did not satisfy the specified range in the mass ratio of the core to the sheath, and the proportion of the core was small, resulting in a low cross-sectional resistance value. [Explanation of Symbols]
[0075] 1. Conductive core-sheath type polyester composite fiber 2 Sheath 3 core 4. Thickness of the sheath
Claims
1. A core-sheath type polyester composite fiber consisting of a core and a sheath, The core portion is composed of a core-forming composition mainly containing polybutylene terephthalate and containing 20 to 35% by mass of a conductive component. The sheath portion is composed of a core-forming composition made of a polyester resin having ethylene terephthalate as the main repeating unit and containing 1 to 15 mol% isophthalic acid per 100 mol% of the acid component. The total fineness is 90 to 400 dtex, the mass ratio of the core to the sheath (core / sheath) in a cross-section perpendicular to the longitudinal direction of the yarn is 35 / 65 to 65 / 35, and the cross-sectional resistance is 5.0 × 10⁻⁶. 3 ~1 x 10 6 A conductive core-sheath type polyester composite fiber with a density of Ω / cm.
2. The conductive core-sheath type polyester composite fiber according to claim 1, wherein the boiling water shrinkage rate is 7% or less.
3. A brush comprising a conductive core-sheath type polyester composite fiber as described in claim 1.
Citation Information
Patent Citations
Cleaning brush and image forming apparatus including the same
JP2014102454A
Conductive core-sheath composite multifilament yarn
JP2016069786A